Rancang Bangun Sistem Notifikasi Sepeda Motor Menggunakan Modul GSM Berbasis Mikrokontroler - Gidion Fajar Tri Krisnadi; Wiwin Sulistyo (Forum Kerjasama Pendidikan Tinggi, 2022)
The notification system for two-wheeled motorcycles is currently very ineffective, so that the theft of motorcycles is very high if they still use an alarm without notification to the owner of the motor vehicle. So that the motorcycle notification system using a GSM module based on a microcontroller can be an alternative to secure motorcycles from theft. The purpose of this study is to make a notification system using the GSM SIM800L module to provide notifications and use an RFID Reader to replace the contact system on a motorcycle. The test results from this study are the performance of the notification system using a GSM module based on this microcontroller can work well. When the RFID receives input from the e-KTP ID Tag and is forwarded to the microcontroller and forwarded to the SIM800L to send an SMS notification, the microcontroller will give the output to the relay to turn on the electricity on the motorcycle.